South Steelbands Get Own Finals - Swamber, Keino (Express)
After failing to make it to the finals of the Bmobile 2007 National Panorama finals, south steelbands will have the opportunity to compete in their own finals. The competition titled "You Be The Judge", is scheduled to be held at Skinner Park, San Fernando. Pan Trinbago's South/Central Regional Chairman Withfield Weekes said it became even more necessary to produce the show because many southerners were disappointed with the national semi-finals results.
Keywords: Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago